Analisis Penggunaan Ice Breaking dengan Metode Brain Gym untuk Mengurangi Rasa Kantuk dan Meningkatkan Konsentrasi Belajar Siswa di Kelas - Agwila Abata; Siska Patattan; Juandi Bilolo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study is motivated by the low level of students’ learning concentration in the classroom, which is reflected in behaviors such as drowsiness, lack of focus, and limited participation during learning activities. These conditions are generally caused by less varied teaching methods and a lack of activities that actively engage students. Therefore, this study aims to examine the use of brain gym–based ice breaking activities to reduce drowsiness and improve students’ concentration. The method employed in this research is a literature review, involving the analysis of various relevant academic sources, including journals, books, and research articles. The findings indicate that integrating ice breaking activities with brain gym techniques has a positive impact on the learning process. This approach is shown to enhance concentration, memory, and students’ readiness to learn. In addition, the simple movements in brain gym can help increase oxygen flow to the brain, making students feel more refreshed and focused. In conclusion, brain gym–based ice breaking can serve as an effective, innovative, and enjoyable instructional strategy to improve the quality of teaching and learning in the classroom.